Medida de atributos físicos do solo por um sensor capacitivo e aplicação no manejo da irrigação da melancia - Oliveira, Antônio Dimas Simão de (2012)
In recent years, with the explosive development of information technology and electronics, the scientific community worldwide has intensified research to develop and implement research-based improvement in precision application. Advances in information technology, especially in the developing of interfaces with electronic sensors, allowed for the development and application of various transducers in Agricultural Engineering. With respect to irrigated farms there is a major concern with the large volume of water used. According to FAO by 2030 it will be required an increase of 14% of drinking water used by irrigation, in order to meet the demand caused by population growth worldwide. In order to improve water use in irrigation, several studies have been and are being developed, especially focused on evaluating, economically, the conversion of water into food and the actual requirement of crops for their full development. The kc is a factor that relates crop water requirement of a real crop to the water requirement of a hypothetical culture. The soil water balance accounts for all additions and withdrawals of water that actually occur in a certain volume of soil used in agricultural production, allowing to access the water situation in which a culture is. From the above, this study aimed to evaluate the use of a capacitive FDR sensor to replace tensiometer in the process of obtaining the crop coefficient (kc) through the soil water balance. The experiment was conducted at the Low Acaraú Irrigation District - Ceará, in an area of 1.0 ha, into two cycles with of watermelon, in the years 2009 and 2010. The sensors were calibrated in the laboratory using regression analysis between soil moisture from a soil sample and frequency produced by the sensor, and between it and the tension found in a mercury based tensiometer, from saturation to approximately 8.0% volumetric water content. The evaluation of the calibration equation occurred by comparing the sensor data and data from tensiometers for moisture and irrigation timing. The calibration equation for both moisture and for the tension was exponential. The comparison between the estimated and measured tensions using the fitted equation produced a strong performance and/or great on all items analyzed. Field validation of the fitted models was conducted by comparative analysis between the frequencies obtained from the FDR sensors and the tensiometers during the first harvesting year. For the second harvesting year, the technique of filter paper was tested. It resulted in the following equations to fit the water retention curves for the soil: θ=0,3843*T^(-0,381) (1st layer), θ=0,4381*T^(-0,372) (2nd layer) and θ=0,4103*T^(-0,34) (3rd layer). In addition, the instantaneous profile method for evaluating the hydraulic conductivity was applied. Were application depth was applied as a treatment for analyzing some physiological characteristics of the crop. The treatments showed statistical differences for stomatal conductance and transpiration, T4 (ϴ= 1.3 of field capacity) being superior to the others to a 0.05 confidence level. kc values ranged between treatments from 0.74 to 1.06 (18 DAP), 0.98 to 1.52 (45 DAP) and 0.67 to 0.85 (59 DAP). Crop yield ranged from 13.019 to 25.867 Mg between treatments. The efficiency of water use ranged from 4.17 to 6.95 kg m-3. The use of the sensor allows for real time measurement of soil water potential and soil moisture, enabling a more secure monitoring and decision making.